PHYSICAL GROWTH PATTERN IN URBAL AND RURAL TODDLERS OF KHORRAM ABAD - Nikpour, S; Massodi, M; ES Hajikazemi; Hosseini, F (Iran University of Medical Sciences, 2000)
Background : The attachment between mother and child is one of the most beautiful relationship which is establishes long before birth. A mother who is attached to her fetus is ready to have a good relationship with her newborn.   Objective : To determine the effect of touching fetus during pregnancy on maternal fetal and maternal newborn attachment.   Design : The study was a single blind controlled clinical trial. Maternal total attachment was measured 2 weeks after abdominal touch in case group and compared with that of control group. Mother's attachment with her newborn was measured at first breast feeding in both groups.   Samples : 100 primigravida mother, 32-35 week pregnant randomly divided in two groups, 50 mothers in case group (with fetal touch) and 50 in control group (without fetal touch)   Results : There was no significant difference between two group regarding fetal attachment behaviors, but maternal newborn attachment behaviors were significantly improved in case group (p=0.000).   Conclusion : Regarding findings, it is suggested that by providing simple interferences, such as touching the fetus on can try to strengthen the relation between mother and her newborn.